Some typical catchment parameters and flow components of rivers on the island of Jawa - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
A general information on catchment parameters and basic flow characteristics is usually needed during the early stage of planning and design of a certain water resources works. Problems may arise due to the absence of basic information for the selection of planning and design stages and methods. Improper knowledge about the systems may mislead to improper decision. An overall study has been done over 30 catchments on the island of Jawa to possibly draw some important basic flow information. This has been done based on data up to 1984. Changes of catchment parameters are believed not to happen, but changes of flow characteristics will certainly present, but will be minimized by selecting variables so that are least influenced by anthropogenic changes. Such an information is not only important in providing overall preliminary view of the systems, but also as a starting postulates for further computation.